2014
DOI: 10.5539/jedp.v4n2p10
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Family Risk and Opportunity Factors and Parent and Child Functioning

Abstract: The effects of socioenvironmental conditions that impede or undermine development (risk factors) and the conditions that promote or enhance development (opportunity factors) were examined in a study of 192 mothers and their one-year-old children. The outcomes constituting the focus of investigation were maternal psychological well-being (positive and negative affect) and child cognitive development. Results showed that the presence of multiple risk factors in the absence of opportunity factors had negative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
8
0
3
Order By: Relevance
“…Furthermore, nuanced interpersonal skills (e.g., verbal and nonverbal acknowledgment) between coach and caregiver have been associated with increased caregiver confidence and competence to engage in collaborative practices with the coach (Jayaraman, Marvin, Knoche, & Bainter, 2015). In addition, Dunst, Trivette, and Hamby (2007) labeled skills such as empathy and positive social interactions as help-giving practices. Furthermore, they found that these skills were strongly related to caregiver satisfaction and highlighted the need for EI providers to be highly trained in relational help-giving skills.…”
Section: Compassionate Care Within the Ei Fieldmentioning
confidence: 99%
“…Furthermore, nuanced interpersonal skills (e.g., verbal and nonverbal acknowledgment) between coach and caregiver have been associated with increased caregiver confidence and competence to engage in collaborative practices with the coach (Jayaraman, Marvin, Knoche, & Bainter, 2015). In addition, Dunst, Trivette, and Hamby (2007) labeled skills such as empathy and positive social interactions as help-giving practices. Furthermore, they found that these skills were strongly related to caregiver satisfaction and highlighted the need for EI providers to be highly trained in relational help-giving skills.…”
Section: Compassionate Care Within the Ei Fieldmentioning
confidence: 99%
“…Terdapat faktor eksternal dan faktor bawaan dari ayah atau ibu yang mempengaruhi kemampuan orang tua dalam menerapkan hal tersebut ketika berinteraksi dengan anak. Menurut Dunst et al, (2014) kondisi lingkungan sosial yang memiliki resiko tinggi (multiple factors) akan berdampak negatif terhadap keberfungsian orang tua. Keluarga dengan faktor resiko yang tinggi akan memicu timbulnya hambatan dalam perkembangan individu di dalam keluarga tersebut.…”
Section: Pendahuluanunclassified
“…Menurut Borlou, Coren, dan Brown (2002) keterampilan pengasuhan (parenting skills) dipengaruhi oleh kesehatan mental orang tua dan hubungan dengan pasangan. Penelitian mengenai kondisi kesehatan mental orang tua dan kualitas pengasuhan telah terbukti memiliki hubungan yang signifikan (Nugraha et al, 2022;Nikolaev et al, 2016;Dunst et al, 2014;Matthew R. SandersMatthew R. SandersJames N. KirbyJames N. Kirby, 2014;Avasthi, 2010). Orang tua yang mengalami depresi, stress, kecemasan, harga diri yang rendah dan hubungan yang buruk dengan pasangan akan berdampak pada timbulnya permasalahan kelekatan anak, emosi, dan keterbatasan perkembangan kognitif pada masa kanak-kanak (Roy,201).. Ibu yang mengalami masalah kesehatan mental berdampak jangka panjang terhadap kesehatan psikologis dan emosi anak (Kanchiputu & Mwale, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Dunst has spent decades conceptualizing and improving both research and practice in the field and has been a leader moving toward a family‐centered approach to services, recognizing the impact that families have in their children's development. Dunst et al (2006) described two dimensions of helpgiving practices (relational and participatory) and both have direct and indirect impacts on child and family outcomes. On the one hand, relational helpgiving refers to interactions with families with respect and empathy with positive beliefs about family strengths.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, social validity evaluates whether telepractice can be considered a feasible evidence‐based practice, according to Reichow et al (2008), and as an indirect quality indicator of family‐centered services. As Dunst et al (2006) pointed out, both direct and indirect effects on child and family outcomes are expected from professional support. Taking social validity as an outcome, we expect capacity‐building practices such as professional–family collaborations, family involvement, and participation to be mediators in the prediction of social validity.…”
Section: Introductionmentioning
confidence: 99%